Protection of minority investors in the capital market: public enforcement and shareholders' litigation - Mohd. Sulaiman, Aiman @ Nariman (Cambridge University Press, 2019)
The capital market provides investors with easy access to wider investment opportunities and provides corporations with wider financing opportunities which should encourage economic growth. The two core values that must exist for a well-functioning capital market are transparency and accountability. Investors’ trust is nurtured and maintained through a regulatory framework that relies primarily on disclosure of material information which is considered by investors to be relevant to their investment decisions, backed by public enforcement by regulators, by quasi-public or self-regulatory organisations and by private enforcement by investors. The disclosure frameworks operates on the basis that whenever an issuer or persons acting on its behalf publicises information about the company, either in relation to an initial public offering or post-listing or under mandatory or voluntary disclosures, the information published is not false or misleading, and there is no material omission of information .Financial misreporting or reporting failures due to disclosure of false or misleading information conveyed to, or in some instances omission of material information from, the market can undermine the integrity of the capital market. The regulatory framework therefore provides for remedies or sanctions where there has been financial misreporting or reporting failures. Malaysia's liability framework enables enforcement actions to be taken by both the regulators and investors against issuers, directors, and other relevant parties involved in the breach of the disclosure obligations. This chapter discusses the liability framework under the common law and capital market legislation in Malaysia with the aim to ascertain the extent to which substantive investor protection rules in Malaysia are enforced. It also discusses whether there are issues or challenges regarding enforcement of compensation claims by investors to recover their losses. This is juxtaposed with disclosure relating to capital raising exercises as well as a company’s periodic and continuous disclosure obligations in Malaysia.